Prevention of maternal aging-associated oocyte aneuploidy and meiotic spindle defects in mice by dietary and genetic strategies - Selesniemi, Kaisa (National Academy of Sciences, 2011)
Increased meiotic spindle abnormalities and aneuploidy in oocytes of women of advanced maternal ages lead to elevated rates of infertility, miscarriage, and trisomic conceptions. Despite the significance of the problem, strategies to sustain oocyte quality with age have remained elusive. Here we report that adult female mice maintained under 40% caloric restriction (CR) did not exhibit aging-related increases in oocyte aneuploidy, chromosomal misalignment on the metaphase plate, meiotic spindle abnormalities, or mitochondrial dysfunction (aggregation, impaired ATP production), all of which occurred in oocytes of age-matched ad libitum-fed controls. The effects of CR on oocyte quality in aging females were reproduced by deletion of the metabolic regulator, peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α). Thus, CR during adulthood or loss of PGC-1α function maintains female germline chromosomal stability and its proper segregation during meiosis, such that ovulated oocytes of aged female mice previously maintained on CR or lacking PGC-1α are comparable to those of young females during prime reproductive life.